Reducing Courts' Failure to Appear Rate: A Procedural Justice Approach (Nebraska Statewide, Select Counties, 2009-2010) - Bornstein, Brian H. ([Verlag nicht ermittelbar], 2011)
The purpose of the study was to examine the effectiveness of using different kinds of written reminders to reduce misdemeanants' failure to appear (FTA) rates. The study examined the problem of FTA via a two-stage experiment. In Phase 1, 7,865 misdemeanor defendants from 14 Nebraska counties were randomly assigned to one of four reminder conditions: (1) a no-reminder (control) condition; (2) a reminder-only condition; (3) a condition in which the reminder also made them aware of possible sanctions should they fail to appear (reminder-sanctions); or (4) a condition in which the reminder mentioned sanctions but also highlighted aspects of procedural justice (PJ), such as voice, neutrality, respect, and public interest (reminder-combined). Data collection began in March 2009 and continued through May 2010. Files were received daily from the Nebraska Administrative Office of the Courts containing information about cases filed in each of the 14 counties included in the study. Upon receipt of this file, researchers screened participants using certain eligibility criteria. Researchers mailed postcard reminders two to five business days prior to the scheduled court appearance. Approximately one week after each scheduled court appearance researchers accessed the courts' administrative database (JUSTICE) to determine whether the defendant actually appeared for the scheduled hearing. Upon accessing this information, researchers recorded this variable, which is the primary dependent variable in the study. At the same time researchers recorded the appearance variable, they selected participants for Phase 2 of the study -- a mail survey administered after their scheduled appearance (or non-appearance) to assess their perceptions of procedural fairness and their level of trust/confidence in the courts. To do so, researchers selected all participants who failed to appear for their court date to receive a survey. Twenty percent of defendants who did appear were also randomly selected to receive a survey. Surveys were sent to a total of 2,360 individuals and were received from a total of 452 defendants. The study contains a total of 197 variables including demographics, court appearance characteristics, experiment characteristics, charge/offense variables, and variables from surveys about experiences with the court system.